Relationship between duration of brain death and hemodynamic (in)stability on progressive dysfunction and increased immunologic activation of donor kidneys. - van der Hoeven, J; Molema, G; Ter Horst, G; Freund, R; Wiersema, J; van Schilfgaarde, R; Leuvenink, H; Ploeg, R (2003)
BACKGROUND: Consistent difference in graft survival after renal transplantation has been shown when cadaveric transplants are compared to the living related donor situation, in favor of the latter. Recently, evidence has been put forward that brain death has significant effects on the donor organ quality. In this study, we aimed to assess the relation between brain death-induced hemodynamic instability in combination with the duration of brain death on the function and immunogenicity status of potential donor kidneys. METHODS: In Wistar rats, short-term (1 hour) or long-term (6 hours) brain death in the presence or absence of hemodynamic stability was applied. Sham-operated rats served as controls (1 hour and 6 hours). Organ function was studied by monitoring serum creatinine, lactate dehydrogenase (LDH), lactate, and total protein content. Expression of cell adhesion molecules [intercellular adhesion molecule-1 (ICAM-1) and vascular cell adhesion molecule-1 (VCAM-1)] and the influx of leukocytes in the kidney assessed the immunologic status of the kidney. RESULTS: Progressive organ dysfunction was most pronounced in hemodynamically unstable brain-dead donors reflected by increased serum creatinine levels. Regardless of hemodynamic status, a progressive inflammatory activation by cell adhesion molecule expression and an influx of leukocytes could be observed in kidneys of brain-dead rats compared with nonbrain-dead controls. CONCLUSION: Brain death causes progressive kidney dysfunction. Also, inflammatory responses reflecting tissue injury are caused by brain death. When hemodynamic instability in the brain-dead donor is not corrected, kidney dysfunction is enhanced and immune activation occurs faster and is more profound. The observed changes may predispose the graft for additional ischemia/reperfusion injury during the transplant process and hence accelerate rejection of the graft after transplantation.